ANALISIS HUBUNGAN STRUKTUR MODAL TERHADAP RENTABILITAS PADA PT. PLN (PERSERO) WILAYAH SULSELBAR - Indrawan Azis (AkMen JURNAL ILMIAH, 2016)
This research aims to clarify the relationship of capital structure towards earning ratiosof PT PLN (Persero) Region Sulselrabar. Whereas the methods of analysis used in this study is the analysis of optimal capital structure, cost of capital is a weighted analysis, analysis of linear correlation analysis of earning ratios, simple. Results of analysis showed that based on a comparison of capital structure of companies with companyearning ratios for 3 years (2012-2014) it appears that the earning ratios declinebecause companies suffered losses. Results of the analysis of the correlation betweencapital structure (DER) and earning ratios of capital structure to see that companieshave a positive relationship but not significant toward earning ratios of the company.